Evaporative water loss in seven species of fossorial rodents: Does effect of degree of fossoriality and sociality exist? - Luna, Facundo; Šumbera, Radim; Okrouhlík, Jan; Mladěnková, Nella; Daniel Antenucci, C (Pergamon - Elsevier Science, Ltd., 2020)
In terrestrial endotherms, evaporation is a significant mechanism of water loss in hot environments. Although water is passively lost by evaporation, individuals can regulate it at different levels. Inhabiting a relatively stable environment characterized by mild ambient temperature (T-a) and high humidity can ensure a balanced water budget. Many fossorial rodents are well adapted to live in such conditions. In this study, evaporative water loss (EWL) of fossorial rodent species with different degree of adaptations to underground life (from strictly subterranean to those with regular surface activity) was evaluated. By measuring EWL, the specific contribution of either evaporative or non-evaporative components of heat loss can be determined. With the exception of the silvery mole-rat (Heliophobius argenteocinereus), in all tested rodents EWL is relatively stable below and within the thermoneutral zone (TNZ). As T(a)s increase above TNZ, EWL increases as does total thermal conductance, but conductance increases several times more than EWL. In addition, non-evaporative routes seem to be more important than evaporative heat loss in the analyzed species. No clear pattern of EWL in relation to a species degree of fossoriality or sociality was detected. In this context, atmosphere of burrows could affect EWL, since the high humidity found inside tunnels can establish limits on evaporation to favor water rather than thermal balance.
Keywords: Evaporative water loss; Thermoregulation; Thermal conductance; Fossorial rodents; Subterranean rodents